2016
DOI: 10.1038/ncomms11495
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical effects in plasmonic structures with subnanometre gaps

Abstract: Metallic structures with nanogap features have proven highly effective as building blocks for plasmonic systems, as they can provide a wide tuning range of operating frequencies and large near-field enhancements. Recent work has shown that quantum mechanical effects such as electron tunnelling and nonlocal screening become important as the gap distances approach the subnanometre length-scale. Such quantum effects challenge the classical picture of nanogap plasmons and have stimulated a number of theoretical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
664
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 691 publications
(685 citation statements)
references
References 134 publications
(264 reference statements)
18
664
2
1
Order By: Relevance
“…Additionally, we experimentally determined the adsorption site area of malachite green to be approximately 2.19 nm 2 , where the average moleculemolecule distance is 1.14 nm. Although these molecules are potentially within the strong coupling regime, 69 we believe the overall spectra are dominated by the plasmon/molecule coupling as evidenced by our good agreement with experiment. For smaller NP's (i.e., < 50 nm), higher site densities, or molecules with higher oscillator strengths, we suspect that the molecule/molecule interaction will play a more important role in the coupling.…”
Section: Parametrizing Monolayer Of Quantum Moleculessupporting
confidence: 72%
“…Additionally, we experimentally determined the adsorption site area of malachite green to be approximately 2.19 nm 2 , where the average moleculemolecule distance is 1.14 nm. Although these molecules are potentially within the strong coupling regime, 69 we believe the overall spectra are dominated by the plasmon/molecule coupling as evidenced by our good agreement with experiment. For smaller NP's (i.e., < 50 nm), higher site densities, or molecules with higher oscillator strengths, we suspect that the molecule/molecule interaction will play a more important role in the coupling.…”
Section: Parametrizing Monolayer Of Quantum Moleculessupporting
confidence: 72%
“…It has recently been reported that the localized plasmons in multiple metal nanostructures reveal interesting phenomena, such as a red-shift of the surface plasmon frequency, large enhancement of the local electric fields, the nonlocal quantum effects and the quantum tunneling effects between the metal nanostructures [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…At the distances between metal particles smaller than few nanometers, the nonlocal response of metals [31] and electron tunnelling effect [36] between the particles become important. Thus, it is expected that, at the distances between emitter and metal surface of 0.5-2 nm, the nonlocality in the metal response is also sensitive.…”
Section: Resultsmentioning
confidence: 99%